2019
DOI: 10.1021/acs.iecr.9b00604
|View full text |Cite
|
Sign up to set email alerts
|

Furfural Production by Continuous Reactive Extraction in a Millireactor under the Taylor Flow Regime

Abstract: This study demonstrates the use of a millireactor as intensified technology for the continuous production of furfural via acid dehydration of xylose in a biphasic media. Very rapid extraction of furfural, aided by fast mass transfer rates, is key to preventing furfural subsequent degradation. Thus, by operating at elevated temperatures (i.e., 150–190 °C), it is possible to maintain high furfural selectivity (ca. 70%) at high xylose conversion (ca. 80%) and very short residence times (up to 2.5 min). A reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…of an intensified reactor with unconventionally high temperatures (i.e., 190 °C vs the conventional 150 °C) was key to a significant reduction in residence time (i.e., from 4−5 h to 3−6 min) and minimal humin formation. 9 Here, the use of process evaluation tools are key to optimize the delicate trade-off between the furfural yield and energy consumption that this process entails while also considering elements such as feed costs, energy, and environmental impact. To this end, robust kinetic models as the backbone of predictive mathematical platforms to reliably describe process performance as a function of operating conditions are essential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…of an intensified reactor with unconventionally high temperatures (i.e., 190 °C vs the conventional 150 °C) was key to a significant reduction in residence time (i.e., from 4−5 h to 3−6 min) and minimal humin formation. 9 Here, the use of process evaluation tools are key to optimize the delicate trade-off between the furfural yield and energy consumption that this process entails while also considering elements such as feed costs, energy, and environmental impact. To this end, robust kinetic models as the backbone of predictive mathematical platforms to reliably describe process performance as a function of operating conditions are essential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…the detailed discussion in Section S1 in the Supporting Information). Papaioannou et al 23 performed xylose conversion over the H 2 SO 4 catalyst in a continuous millireactor (inner diameter: 4.1 mm) at a short residence time of 2.5 min. The STY FF is satisfactory (19.9 mol min −1 m −3 ), but the furfural yield (ca.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Comparatively, few reports have been published on its application for furfural synthesis. One recent work is from Papaioannou et al 23 who demonstrated xylose conversion to furfural over the H 2 SO 4 catalyst in water-toluene biphasic systems in a slug flow millireactor (inner diameter: 4.1 mm). The furfural extraction aided by the strong inner circulation within aqueous droplets and organic slugs is claimed to greatly prevent furfural degradation.…”
mentioning
confidence: 99%
“…The concept of biphasic operation, based on the process of reactive extraction, exploits the continuous liquid-liquid extraction of the formed HMF or furfural into the organic phase. [78][79][80][81][82] The characteristics of these biphasic systems are variable in terms of catalysis and composition. 31,40,73,75 While homogeneous catalysis by mineral acids remains the preferred source, in several studies heterogeneous catalysis has also been successfully applied at biphasic conditions.…”
Section: Reaction Towards Humins and Other By-productsmentioning
confidence: 99%